The impact of service quality on business commitment in B2B segment of agribusiness: an exploratory study of HORECA sector in Malaysia - Tey, Yeong Sheng; Brindal, Mark Kennion; Mohamed Arshad, Fatimah; Mohd Noh, Kusairi; Abdul Hadi, Ahmad Hanis Izani; Darham, Suryani (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
In competitive markets, agribusiness firms have embarked on improving their service quality for building and maintaining a profitable relationship with their customers. However, such impact of service quality on business commitment has not been empirically investigated. To fill this gap, this study explores the relationship between service quality and commitment, using a case of supplier selection of fresh produce by hotel, restaurant, and catering (HORECA) sector in Malaysia. Using SERVQUAL as the main component of the conceptual framework, the relevant information was collected from 195 random HORECA operators and analyzed using partial least squares. The results indicate that service quality explains little of HORECA's decision to stay with their current suppliers. While most service quality factors were insignificant, "responsiveness" in term of providing delivery service had a statistically significant positive impact on HORECA's contractual arrangement with their current suppliers. These findings imply that quality service is being seen as a supplement; economic factors (e.g., prices and their stability, credit term) are likely to be the key drivers affecting buyer-seller relationships. If suppliers want to stay on course, they have to improve their service quality and focus more on delivery service. In addition, more research is needed in this relatively new area.